Embalagem ativa com extratos naturais contra microrganismos patogênicos e deteriorantes - Balbé, Naiana Pereira (2025)
Packaging is intended to preserve food and its nutrients, prevent physical, chemical and microorganism contamination during handling and, therefore, improve the shelf life of food. From the point of view of increasingly conscious consumers, who opt for healthier, higher quality and safer food, green packaging presents itself as a more sustainable alternative to packaging from non-renewable sources. Plastic was created in 1990 and, since then, has been used in various segments in packaging. However, because it is derived from a fossil fuel, petroleum, it has some disadvantages, such as availability, degradability, recycling, among others. Natural polymers are an alternative to replace such materials, due to their high availability in nature, such as, for example, from the valorization of a starchy industrial residue, where starch is the natural polymer matrix. In this study, the synthesis of an intelligent packaging was evaluated, added with natural extracts of butiá, araçá, uvaia and guabiroba and commercial extracts of oregano and eucalyptus in different concentrations in order to prove its inhibitory capacity of pathogenic and deteriorating microorganisms. All six extracts showed action against the gram-positive microorganisms tested (Staphylococcus aureus, Staphylococcus epidermidis, Listeria inoccua, Listeria monocytogenes, Enterococcus faecalis). For the continuation of the work, it was decided to choose the extracts of eucalyptus, guabiroba and uvaia in different concentrations in the film-forming solution that varied from 10% to 25%, however, there were no significant differences in relation to the growth halo, when compared to the control (ampicillin 10mg/mL). Afterwards, the applicability of the film-forming solution as packaging was tested by coating a test specimen (chicken meat), based on experimental treatments. In response, there was a decrease in the growth of Listeria monocytogenes, when compared to the untreated control, but the difference was not significant, which suggests that further studies should be carried out in order to expand knowledge about the application of packaging in food matrices.